A review on the effects of probiotics and antibiotics towards Clostridium difficile infections - Azman, Hazirah; Loong, Yik Yee; Abdul Aziz, Rushdan; Awang Hamat, Rukman; Abd Manap, Mohd Yazid (Universiti Putra Malaysia Press, 2013)
Clostridium difficile can cause severe diseases with significant morbidity and mortality in infected patients. The rate of Clostridium difficile infection is high in North America and European countries. Metronidazole and vancomycin have been recommended as the treatments of choice since 1990s. Recurrent infection due to Clostridium difficile is common after several days of antibiotic administration. Probiotics have been used in these patients as an adjunct treatment with some successful findings. However, a detailed investigation on the use of probiotic for infected patients is still needed, particularly for its real efficacy.